Metabolic syndrome, inflammation and atherothrombosis - Rohla, M.; Weiss, T. W. (Hämostaseologie, 2013)
Extensive research of the past decades altered our traditional concept about the genesis of atherosclerosis fundamentally. Today, the crucial role of inflammation in the formation and progression of atherosclerotic plaques is indisputable. Patients at high risk for developing cardiovascular disease, owing to poor diet, obesity and low physical activity have been shown to exhibit a particular inflammatory pattern.Therefore, the present review highlights the crosslink between the metabolic syndrome (MetS), adipose tissue, adipokines and selected inflammatory cytokines in the context of atherothrombosis and cardiovascular disease.
Keywords: Metabolic syndrome; cardiovascular disease inflammation; atherosclerosis